Moisture distribution model describes the effect of water content on the structural properties of lotus seed resistant starch. (15th July 2019) - Chen, Chuanjie; Fu, Weiqing; Chang, Qing; Zheng, Baodong; Zhang, Yi; Zeng, Hongliang
Highlights: The structural properties of LRS were affected by the initial moisture content. Proper water content (70% and 80%) helped the ordered structure formation of LRS. Bound water was related to the hydrated starch chains. Channel water in B-type crystal was in line with the micro-crystalline structure. The structural properties of LRS can be depicted by moisture distribution model. Abstract: The objective was to utilize a moisture distribution model to summarize the influence of water content on the structural properties of lotus seed resistant starch. The result showed that water content affected the composition of resistant starch. The compact structure was observed on the surface of resistant starch prepared with 50% water content; other samples displayed a flake structure. Compared with samples prepared with insufficient (50% and 60%) or excess water (95% and 90%), resistant starches prepared with 70% and 80% water content were composed of higher-molecular-weight chains and consisted of more double helix and crystal. Two corresponding relationships between the structural properties of resistant starch and the water distribution in them were found. Bound water was related to the hydrated starch chains, while channel water in B-type crystal represented the micro-crystalline structure. Therefore, moisture distribution model can be feasibly used to depict the structural properties of resistant starch.